The impact of health education interventions on HPV vaccination uptake, awareness, and acceptance among people under 30 years old in India: a literature review with systematic search - Krokidi, Eleni; Rao, Arathi P.; Ambrosino, Elena; Thomas, Pierre P. M. (Frontiers in Reproductive Health, 2023)
Background: The HPV vaccine is used as one of the main prevention tools for HPV-related cancers globally, yet it is not part of the Indian National Immunization program. In light of the introduction of the indigenous vaccine, we examine the effectiveness of health education about uptake, acceptance, and awareness. Methods: Research was performed in the following databases: PubMed, CINAHL, Scopus, and Embase to identify studies between 2008 and 2022. Studies were included if: they were conducted in India including primary data research and health education intervention, and participants were between 9 and 29 years old. Results: Out of the 10.952 results, 7 studies were included. Four studies focused on adolescent girls, aged from 9 to 20 years old, and 3 on university students aged from 17 to 26 years. Five studies were implemented in urban areas and 2 in rural areas. Health education interventions proved to be effective in increasing uptake, awareness, and acceptance of the HPV vaccine. The barriers included among others: cost, lack of awareness, and cultural barriers. Conclusion: Observations from this study outline immediate action for policymakers to educate and encourage the young population toward HPV vaccination. Future programs should be aimed at different population groups and be adjusted according to their special characteristics and needs. Attention should be given to the male population and marginalized groups. The involvement of various stakeholders proved to be beneficial, and it is highly recommended.